Market Segmentation Methodology: segmentation basis and classification methods - Oliveira-Brochado, Ana; Martins, Francisco Vitorino (Review of Business Management, 2008)
This work provides a comprehensive review of the literature on market segmentation, focusing on the discussion of proposed bases and classification methods. Multiple segmentation bases are detached, organized according to two axes - observable/ unobservable, general/specific of the product - and evaluated according to some criteria that must be satisfied for an effective segmentation: identifiability, substantiality, accessibility, stability, actionability and responsiveness. Classification methods are also grouped in three classes - nonoverlapping, overlapping and fuzzy, according to the format of the partition matrix they provide. Key-words: Market segmentation. Effective segmentation. Segmentation bases. Classification analysis.